The cerebrum and cerebellum of Rattus norvegicus offspring, whose mothers were exposed to a sequence of 14 Mozart compositions during pregnancy, expressed higher levels of BDNF and dendritic density, but not mTORC1 - Hermanto TJ; N Cininta M; Widjiati (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: To investigate Brain-Derived Neurotrophic Factor levels, Mammalian Target of Rapamycin Complex 1 levels, and Dendritic Density in the cerebrum and cerebellum of Rattus norvegicus offspring following prenatal Mozart compositions exposure. Material and Methods: An experimental study with a randomized post-test-only control group design was conducted at the Animal Laboratory of the Faculty of Veterinary Medicine, Universitas Airlangga, following ethical clearance. A 13 healthy pregnant female Rattus norvegicus were randomly chosen and exposed to 14 Mozart compositions, beginning on gestation day 10 until delivery, while another 13 served as the control group. At day 20, the rats were sacrificed, 2 offsprings' brains (the heaviest) were extracted, and BDNF levels were analyzed using the ab203573 immunohistochemistry kit, mTORC1 levels using the pSer2448 kit, and Dendritic Density using silver impregnation. Statistical analysis was performed accordingly with a significance level of p < 0.05. Results: BDNF levels and Dendritic density in the cerebrum of the treatment group were higher (2.27 ± 1.41 vs. tr 7.44 ± 2.09, p < 0.05) and (4.42 ± 2.04 vs. 6.67 ± 1.23, p < 0.05). In the cerebellum, BDNF levels and Dendritic density in the treatment group were higher (1 vs. 8, p < 0.05) and (3.34 ± 1.94 and 7.91 ± 2.45, p < 0.05). mTORC1 levels in the treatment group were lower but not statistically significant in both areas. Conclusion: Prenatal 14 Mozart compositions exposure during pregnancy increased Rattus norvegicus offsprings' cerebrum and cerebellum BDNF levels and Dendritic Density. A correlation was found between BDNF levels and dendritic density.